On exo-cyclic aromaticity. Issue 19 (27th April 2017) - Goswami, Tamal; Homray, Manoswita; Paul, Satadal; Bhattacharya, Debojit; Misra, Anirban
Abstract : The C2 B2 F4 molecule shows the tendency of attaining the aromatic 'sextet', through an ' exo -cyclic' conjugation. Abstract : The domain of aromaticity spans a wide range of molecules, from polycyclic aromatic hydrocarbons, heterocycles to all-metal systems. Here, in silico we demonstrate the aromaticity in C2 B2 F4, extending beyond the limit of conventional aromatic molecules. This molecule gains the magic number of six π-electrons through an unusual electronic contribution from exo -cyclic atoms. The stability of the molecule is established through density functional theory, ab initio calculations as well as molecular dynamics simulation.